Peltier cooling of superconducting current leads - Gehring, F.K.; Hüttner, M.E.; Huebener, R.P. (Cryogenics (Guildford), 2001)
An interesting application of Peltier cooling based on the Peltier materials presently available arises for the cooling of current leads connected to superconducting power electronics. By inserting n-doped and p-doped Peltier tablets at the warm end into the circuit, at their warm side the remaining current leads can be Peltier cooled about 50–60 K below room temperature. We have developed an experimental test apparatus for dc operation up to a current of 200 A. Our experiments, performed with Peltier tablets fabricated from n-doped and p-doped Bi 2Te 3, well confirmed the expected Peltier cooling. From our results we estimate the reduction of the thermal losses (by typically 13%) and of the electric power losses (by typically 10%) due to the insertion of the Peltier tablets. In addition to the dc experiments, we have also carried out similar experiments using 50 Hz ac and a bridge circuit yielding a rectified output current. Minimization of the electric contact resistance generated at the surfaces of the Peltier tablets (and of the rectifying diodes required for ac operation) represents an important issue.